Pengaruh Lingkungan Kerja Dan Pengembangan Karir Terhadap Employee Engagement Karyawan Di Fave Hotel Olo Padang - Martin Karim; Youmil Abrian (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Based on KPI data at Fave Hotel Olo Padang regarding employees, problems were found with employee performance levels that occurred from June 2023 to August 2023. These performance problems consisted of problems in the work environment, career development and employee engagement. This causes a lack of work effectiveness of employees. The objective of this study is to examine the impact of the working environment and career development on employee engagement at Fave Hotel Olo Padang. The category of research that author conducted was quantitative using a causal associative approach with a survey method, this was used to determine the influence of the Work Environment (X1), Career Development (X2), on Employee Engagement (Y). The population of this research is employees at Fave Hotel Olo Padang. The sample for this research consisted of 45 respondents and used a sampling technique in the form of closed questions which were given to respondents directly. The independent variables examined in this research are Work Environment and Career Development with respect to the dependent variable, namely Employee Engagement, using PLS-SEM analysis techniques and data description. The results of this research show that the Work Environment and Career Development variables have a positive effect on Employee Engagement.